Knowledge, attitude and practices of diabetic patients in the United Arab Emirates. - Fatma Al-Maskari; Mohamed El-Sadig; Juma M Al-Kaabi; Bachar Afandi; Nicolas Nagelkerke; Karin B Yeatts (PLoS ONE, 2013)
INTRODUCTION: Diabetes self-management education is a cornerstone of diabetes care. However, many diabetics in the United Arab Emirates (UAE) lack sufficient knowledge about their disease due to illiteracy. Thus, before considering any possible intervention it was imperative to assess present knowledge, attitudes, and practices of patients towards the management of diabetes. METHODS: A random sample of 575 DM patients was selected from diabetes outpatient's clinics of Tawam and Al-Ain hospitals in Al-Ain city (UAE) during 2006-2007, and their knowledge attitude and practice assessed using a questionnaire modified from the Michigan Diabetes Research Training Center instrument. RESULTS: Thirty-one percent of patients had poor knowledge of diabetes. Seventy-two had negative attitudes towards having the disease and 57% had HbA(1c) levels reflecting poor glycemic control. Only seventeen percent reported having adequate blood sugar control, while 10% admitted non-compliance with their medications. Knowledge, practice and attitude scores were all statistically significantly positively, but rather weakly, associated, but none of these scores was significantly correlated with HbA(1c). CONCLUSIONS: The study showed low levels of diabetes awareness but positive attitudes towards the importance of DM care and satisfactory diabetes practices in the UAE. Programs to increase patients' awareness about DM are essential for all diabetics in the UAE in order to improve their understanding, compliance and management and, thereby, their ability to cope with the disease.